A new species of Otothyropsis (Siluriformes: Loricariidae) from the rio Paraguay basin, Paraguay - Calegari,Bárbara B. (2011)
Otothyropsis piribebuy, new species, is described from the río Piribebuy, a tributary to the río Paraguay basin, Cordillera, Paraguay. The new species is distinguished from O. marapoama mainly by having a continuous mid-dorsal series of 17-18 lateral plates, a robust levator crest in the hyomandibula, naked areas in the abdomen, an unpigmented circular blotch on the median portion of the lower lobe, and by several features related to sexual dimorphism. In addition, Otothyropsis is re-diagnosed and its phylogenetic relationships are discussed based on its present diversity.